2007
DOI: 10.4049/jimmunol.178.11.7344
|View full text |Cite
|
Sign up to set email alerts
|

The MYD88-Independent Pathway Is Not Mobilized in Human Neutrophils Stimulated via TLR4

Abstract: LPS activates both MyD88-dependent and -independent signaling via TLR4, but the extent to which each cascade is operative in different cell types remains unclear. This prompted us to revisit the intriguing issue of CXCL10 production, which we previously showed to be inducible in neutrophils stimulated with LPS and IFN-γ but not with either stimulus alone, contrary to other myeloid cells. We now report that in neutrophils the MyD88-independent pathway is not activated by LPS. Indeed, microarray and real-time PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

16
112
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 104 publications
(131 citation statements)
references
References 82 publications
16
112
3
Order By: Relevance
“…In keeping with the inability of neutrophils to produce IFN-b, we have already shown that the activation of IRF-3 is not inducible in IFN-c plus LPS-treated neutrophils [11]. We have also shown that neutrophils express little or no c-Jun, a key component of AP-1 complexes, and that consequently, AP-1 is not inducible by LPS and/or IFN-c in these cells [11,18]. Consequently, we reasoned that a possible mechanism leading to the stronger induction of CXCL10 gene by the LPS plus IFN-c combination in neutrophils could be a synergistic enhancement of IFN-c-induced STAT1 tyrosine phosphorylation and, in turn, STAT1-containing DNAbinding activities exerted by LPS.…”
supporting
confidence: 66%
See 4 more Smart Citations
“…In keeping with the inability of neutrophils to produce IFN-b, we have already shown that the activation of IRF-3 is not inducible in IFN-c plus LPS-treated neutrophils [11]. We have also shown that neutrophils express little or no c-Jun, a key component of AP-1 complexes, and that consequently, AP-1 is not inducible by LPS and/or IFN-c in these cells [11,18]. Consequently, we reasoned that a possible mechanism leading to the stronger induction of CXCL10 gene by the LPS plus IFN-c combination in neutrophils could be a synergistic enhancement of IFN-c-induced STAT1 tyrosine phosphorylation and, in turn, STAT1-containing DNAbinding activities exerted by LPS.…”
supporting
confidence: 66%
“…Finally, our data do not exclude that the induction of CXCL10 mRNA expression by IFN-c and LPS in neutrophils might also be favored because it is not counter regulated by attenuators of cytokine-induced responses, such as the SOCS proteins [29]. Indeed, our previous observations have shown that in contrast to monocytes, neither SOCS-1 nor SOCS-3 protein expression is induced by LPS in neutrophils [11,30].Conversely, it appears that monocyte responses are attenuated by LPS-activated SOCS-1/SOCS-3, since the induction of CXCL10 mRNA expression by IFN-c plus LPS is much lower than that exerted by IFN-c alone [6]. Interestingly, the reason why SOCS-1 is not inducible by LPS in neutrophils derives from the lack of mobilization of the MyD88-independent pathway, which controls SOCS-1 gene via endogenous .…”
contrasting
confidence: 64%
See 3 more Smart Citations